Female Circumcision in Banjar Culture: Navigating Customary Law, Islamic Law, and Human Rights - Muzainah, Gusti; Firqah Annajiyah Mansyuroh; Rusdiyah, Rusdiyah; Azhar, Alias (Al-Ahkam, 2025)
This study examines the practice of female circumcision (basunat) among Banjar communities in South Kalimantan-Indonesia, where customary law and Islamic belief intersect with global human rights discourse. The research addresses the legal tension between the international prohibition of Female Genital Mutilation (FGM) and local acceptance grounded in 'urf and maqāṣid al-sharī‘a. Using a normative legal approach supported by qualitative field data—interviews, local regulations, and fiqh analysis—the study reveals that basunat is a purely symbolic, non-cutting, and non-invasive ritual performed hygienically by trained midwives. Distinct from FGM, it functions as a rite of purification and moral responsibility, strengthening social cohesion and spiritual identity. The findings demonstrate a form of localized legal consciousness that reconciles cultural practice with Islamic legal reasoning. The study contributes to scholarship on legal pluralism, urging context-sensitive legal frameworks that differentiate symbolic basunat from FGM while safeguarding both human rights and cultural heritage in pluralistic societies.